Sosial Media Marketing Effects on Kahf Purchase Intention: Brand Image, Trust, and Perceived Risk - Mumtahanah Hujjah Rahmayunita; Lilik Noor Yuliati; Popong Nurhayati (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Social media marketing is a marketing strategy that is widely used by business people through social media platforms such as Instagram to increase purchasing interest and reduce consumer perceived risk. Based on the revenue market skincare in Indonesia will also continue to increase. It is undeniable that more and more people are aware of the importance of maintaining the health and appearance of their skin. Awareness of appearance and skin health does not only apply to women. Men also want to look and feel good about themselves, and skin care can help improve their appearance.Purpose: This study aims to explore the effects of social media marketing on brand image, brand trust, and perceived risk, and how these factors influence purchase intentions. In addition, it seeks to assess the mediating role of brand image, brand trust, and perceived risk between social media marketing and purchase intention. Design/methodology/approach: This study employed a quantitative approach, using non-probability voluntary sampling, with a total of 220 male respondents who had visited Kahf's Instagram account. Data were collected through an online questionnaire distributed using Populix and analyzed using Structural Equation Modeling (SEM) with AMOS software. Findings/Result: The results showed that social media marketing significantly affects brand image, brand trust, and perceived risk. Moreover, brand trust and perceived risk have a significant impact on purchase intention. The mediating variable brand trust significantly mediates the relationship between social media marketing and purchase intention. Conclusion: Social media marketing is one of the marketing that can influence a brand image, brand trust and perceived risk of consumers. By increasing social media marketing, brand trust, and perceived risk will increase consumer buying interest.Originality/value (State of the art): This study is the first study to analyze purchase intention by adding perceived risk variables as intervening variables. Keywords:   brand image, brand trust, perceived risk, purchase intention, social media marketing